Liquid criminology doing imaginative criminological research - Jacobsen, Michael Hviid; Walklate, Sandra (Routledge/Taylor & Francis Group, 2017)
Liquid Criminology sheds light on a way of doing research for criminology that is not only creative but also critical. As such, it will appeal to scholars of sociology, criminology and social policy with interests in research methods and design.